Malaysia SME Program Efficiency Review - Kuriakose, Smita (The World Bank, 2022)
With Small and Medium Enterprises (SMEs) constituting a large proportion of Malaysian enterprises and making significant contributions to employment, GDP, and exports, it is vital for the achievement of Malaysia's development aspirations that these SMEs are enabled to achieve higher levels of productivity and performance. Malaysian firms in general, but most particularly its SMEs, face a number of fundamental issues and challenges related to innovation and the adoption and effective use of new technologies. The effects of the rapid evolution of the modern business environment that have resulted from the introduction of innovative new technologies and business practices have been exacerbated by the current high level of uncertainty related to the pandemic, placing increased emphasis on the need to improve firm capabilities. The Coronavirus (COVID-19) crisis has forced businesses to adapt and adopt digital tools in order to operate in the current environment. Given the considerable fiscal challenges resulting from the pandemic, there is an urgent need to recalibrate Malaysia's provision of public support for SMEs to enable the post-pandemic recovery to be driven by the private sector. In this context, the overall objective of this study is to analyse the composition of Malaysia's SME and entrepreneurship support policies so as to identify opportunities to decrease redundancies and to increase efficiencies by ensuring that public support towards SME development responds effectively to the most pressing needs of SMEs
Keywords: E-Finance and E-Security; Finance and Financial Sector Development; Financial Regulation and Supervision; Gross Domestic Product; Rural Development; Science and Technology Development; Technology Innovation